Recurrent adnexal torsion in a teenager with hypermobile Ehlers-Danlos syndrome: A case report - Michail Panagiotopoulos; Maria Tsiriva; Lito Vogiatzi-Vokotopoulou; Konstantinos Koukoumpanis; Nikolaos Kathopoulis; Athanasios Douligeris; Athanasios Protopapas; Lina Michala (Case Reports in Women's Health)
Hypermobile Ehlers-Danlos syndrome (hEDS) is the most common type of EDS, characterized by joint hypermobility, frequent dislocations, and chronic pain. Genetic markers are not typically used in diagnosis.A 17-year-old clinically diagnosed with hEDS presented with recurrent lower abdominal pain, later attributed to intermittent partial adnexal torsion. Whole-genome sequencing revealed a missense mutation c.1691G > A (p.Arg564His) in the COL1A1 gene. She had undergone two exploratory laparotomies at ages 8 and 10 due to acute pain, resulting in a left adnexectomy and right detorsion with hydrosalpinx drainage. It was suspected that the recurrent adnexal torsion was linked to hEDS-related tissue elasticity, and so a laparoscopic right oophoropexy by shortening the utero-ovarian ligament was performed. At one-year follow-up, she was asymptomatic.This case highlights the potential connection between hEDS and adnexal torsion, which may contribute to chronic abdominal pain, often misattributed to other conditions, such as irritable bowel syndrome.